Pengaruh EPS, ROA, DAN CR Terhadap Harga Saham Perusahaan Makanan Dan Minuman - Risma Khairunnisa; Immas Nurhayati; Renea Shinta Aminda (CV. ITTC INDONESIA, 2023)
This study aims to determine the effect of Earnings Per Share, Return on Assets, and Current Ratio on the share prices. The objects in this study are all companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange for the 2017-2021 period. The sampling method used was purposive sampling and the number of samples used was 12 companies. The type of data used is quantitative data and data sources using secondary data obtained through the official website of the Indonesia Stock Exchange. The data analysis methods used to test the hypothesis in this study are multiple linear regression analysis, hypothesis test, and determination coefficient analysis. The results showed that partially Earnings Per Share did not have a significant effect on stock prices, Return on Assets did not have a significant effect on stock prices, and Current Ratio had a significant effect on stock prices. Simultaneously, all independent variables have a significant effect on stock prices. The result of the coefficient of determination is obtained R-square (R2) value of 0.950939 or 95.09%, meaning that independent variables, namely Earnings Per Share, Return on Assets, and Current Ratio are able to explain the dependent variable, namely the stock price of 95.09%. While the remaining 4.91% is explained by other variables that are not included in this regression model.